Screening antibacterial activity ODS fractions of marine sponges against non-pathogenic bacteria tuberculosis Mycobacterium smegmatis - Sumilat, Deiske A. (Universitas Sam Ratulangi, 2021)
Nine unidentified marine sponges from Bunaken Island waters in Manado Indonesia were observed on anti-tuberculosis (TB) against non-pathogenic Mycobacterium smegmatis NBRC 3207 and it was found that the ethanol crude extracts and ODS fractions of these sponges inhibited the growth of bacteria M. smegmatis. Sponge SP.323 is the most inhibiting and showed Intermediate (I) activity with inhibition zones of 9, 11, 11, 8 mm/disk at 10Âµg/disk., for fraction 3,4,5,6 respectively, and need further experimental analysis to justify the antimicrobial activity, NMR analysis and structure elucidation.